Tetrameristaceae (Angiospermae: Ericales): First record of the family in Brazil - Viana, Pedro Lage; Carvalho, Fernanda Antunes; Silva, Isabel Reis (Revista Brasileira de Botanica, 2010)
Tetrameristaceae is a small Angiosperm family included in Ericales clade with three known genera, Tetramerista, Pentamerista and Pelliciera, never recorded before in Brazil. Biological inventories carried out at the Madeira - Purus rivers interfluvial region from April to June 2007, recorded the occurrence of Pentamerista neotropica Maguire in Brazil, which is the first citation of Tetrameristaceae family in this country. This record is approximately 1.000 km distant from the localities where this species has been previously recorded. This kind of discovery demonstrates the necessity of more fieldwork towards a better knowledge of plant diversity in the Brazilian Amazon forest.
Tetrameristaceae (Angiospermae: Ericales): Primeiro registro da família para o Brasil
Keywords: Ericales; Magnoliophyta; Pelliciera; Pentamerista; Pentamerista Neotropica; Tetramerista; Tetrameristaceae